(E)-3-(2,6-Dichlorophenyl)-1-(4-methoxyphenyl)prop-2-en-1-one - Benmekhbi, Lotfi (International Union of Crystallography, 2009)
In the title compound, C(16)H(12)Cl(2)O(2), the dichlorophenyl and methoxyphenyl groups are linked by a prop-2-en-1-one group. The C=C double bond is trans configured. The molecule is not planar, as can be seen from the dihedral angle of 6.21 (7)° between the planes of the two rings. The crystal structure can be described by two types of crossed layers which are parallel to (110) and (1[Image: see text]0).